Differences in physical fitness and gross motor coordination in boys aged 6-12 years specializing in one versus sampling more than one sport - Fransen, J.; Pion, J.; Vandendriessche, J.; Vandorpe, B.; Vaeyens, R.; Lenoir, M.; Philippaerts, R. M. (Journal of Sports Sciences, 2012)
The Developmental Model of Sports Participation proposes two pathways towards expertise in sports between 6 and 12 years of age: early specialization and early diversification. This study investigated the effect of sampling various sports and of spending many or few hours in sports on fitness and gross motor coordination. Altogether, 735 boys in three age groups (6-8, 8-10, and 10-12 years) were profiled using a fitness test battery. A computerized physical activity questionnaire was used to obtain data on sports participation. In the eldest group, (M)ANCOVA showed a positive effect of sampling various sports on strength, speed, endurance, and gross motor coordination (P < 0.05). A positive effect of many hours per week spent in sports was apparent in every age group. These data suggest an acute positive effect of many hours in sports and a latent positive effect of early sampling on fitness and gross motor coordination. Multiple comparisons revealed that boys aged 10-12 years, who spent many hours in various sports, performed better on standing broad jump (P < 0.05) and gross motor coordination (P < 0.05) than boys specializing in a single sport. Therefore, our results highlight the importance of spending many hours in sports and sampling various sports in the development of fitness and gross motor coordination.